Physics for Matriculation. - Poh, Liong Yong (HBR's 10 must reads (Series), 2019)
"The best leaders know how to communicate clearly and persuasively. How do you stack up? If you read nothing else on communicating effectively, read these 10 articles. We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you express your ideas with clarity and impact--no matter what the situation. Leading experts such as Deborah Tannen, Jay Conger, and Nick Morgan provide the insights and advice you need to: (1) Pitch your brilliant idea--successfully, (2) Connect with your audience, (3) Establish credibility, (4) Inspire others to carry out your vision, (5) Adapt to stakeholders' decision-making styles, (6) Frame goals around common interests, and (7) Build consensus and win support. This collection was previously published as "Harvard Business Review on Communicating Effectively." We've moved it to HBR's 10 Must Reads series because the ideas are critical to the success of every manager and aspiring leader, meeting our high standards for must-read status."--Publisher's website.